We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
88
1
avatar+256 

y = 2x - 2

y = x^2 + 2x - 3

 Jun 11, 2019

Best Answer 

 #1
avatar+129 
+1

First set them equil to each other

2x-2=x^2+2x-3

Subtract 2x from each side

-2=x^2-3

Add 3

1=x^2

Take the square root

x=+-1

 

Now plug both values of x into the equation to find y

 

x=1

y=2x-2

Substitute 1 for x

y=2(1)-2

y=2-2

y=0

One of the solitutions is the point (1,0)

 

x=-1

y=2x-2

Substitute -1 for x

y=2(-1)-2

y=-2-2

y=-4

The other solitution is (-1,-4)

 Jun 11, 2019
 #1
avatar+129 
+1
Best Answer

First set them equil to each other

2x-2=x^2+2x-3

Subtract 2x from each side

-2=x^2-3

Add 3

1=x^2

Take the square root

x=+-1

 

Now plug both values of x into the equation to find y

 

x=1

y=2x-2

Substitute 1 for x

y=2(1)-2

y=2-2

y=0

One of the solitutions is the point (1,0)

 

x=-1

y=2x-2

Substitute -1 for x

y=2(-1)-2

y=-2-2

y=-4

The other solitution is (-1,-4)

power27 Jun 11, 2019

23 Online Users

avatar
avatar